2018
DOI: 10.1063/1.5022184
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a double-grating interferometer for phase-contrast computed tomography in a conventional system nanotom® m

Abstract: Visualizing the internal architecture of large soft tissue specimens within the laboratory environment in a label-free manner is challenging, as the conventional absorption-contrast tomography yields a poor contrast. In this communication, we present the integration of an X-ray double-grating interferometer (XDGI) into an advanced, commercially available micro computed tomography system nanotom ® m with a transmission X-ray source and a micrometer-sized focal spot. The performance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Third, PCCT could provide detailed 3D vascular morphologic information and acquire a larger field of view (FOV) than liver biopsy, but the FOV is still smaller than clinical CT. Recent research has shown that PCI could be available in commercial CT systems with a larger FOV (40). Also, the imaging of the smallest capillaries with sizes below 4 μm is still limited by the resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Third, PCCT could provide detailed 3D vascular morphologic information and acquire a larger field of view (FOV) than liver biopsy, but the FOV is still smaller than clinical CT. Recent research has shown that PCI could be available in commercial CT systems with a larger FOV (40). Also, the imaging of the smallest capillaries with sizes below 4 μm is still limited by the resolution.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-modal comparison of different imaging methods for the characterization of cartilage degeneration revealed additional quantitative information on morphology and ultra-structure by GBPC-CT compared to MRI [156]. Khimchenko et al presented electron density GBPC-CT images of cartilage and bone using an adapted commercial micro-CT system [114]. Perfusion of ischemic kidneys was analyzed with X-ray phase contrast imaging in [157].…”
Section: Applications Of Quantitative Gbpc-ctmentioning
confidence: 99%
“…This so-called source grating is an absorption grating which provides sufficient partial coherence for the method to work with extended X-ray sources like clinical X-ray tubes [ 27 ]. As an alternative to the source grating, one can also utilize micro focus X-ray source with small focal spot sizes [ 113 , 114 ] or a structured anode [ 115 , 116 ].…”
Section: Grating Interferometrymentioning
confidence: 99%
“…However, commercial systems present many obstacles to such modifications, particularly due to their compact nature with respect to custom systems. In this work, we discuss the design of the XDGI setup in a commercial µCT system and demonstrate its operation [2].…”
mentioning
confidence: 99%
“…Visibility map of the XDGI setup (a) and cross-sections of a human knee joint obtained with a commercial laboratory µCT-system equipped with the described XDGI, for phase contrast (b). Simultaneously acquired absorption contrast (c) and optimized, dedicated absorption contrast measurements (d) in the same system show reduced contrast in cartilage (white arrow in b) [2].…”
mentioning
confidence: 99%